2023
DOI: 10.1002/1878-0261.13372
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond pulsed electric field ablation‐induced modulation of sphingolipid metabolism is associated with Ly6c2+ mononuclear phagocyte differentiation in liver cancer

Abstract: Preclinical studies have proven that nanosecond pulsed electric field (nsPEF) ablation can be a safe and effective treatment for humans with unresectable liver cancer that are ineligible for thermal ablation. The concomitant activation of antitumor immunity by nsPEF can also potentially prevent tumor recurrence. However, whether nsPEF exhibits similar efficacy in a clinical setting remains to be investigated. A prospective clinical trial (http://clinicaltrials.gov identifier: NCT04039747) was conducted to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Initial trials in humans have also demonstrated the feasibility of nsPEF for the treatment of other cutaneous lesions such as seborrheic keratosis and sebaceous gland hyperplasia [76,77]. Clinical studies on applications for visceral organs are limited; however, Liu and colleagues [78] have trialed nsPEF for treating hepatocellular carcinoma (HCC) in 15 patients [79]. Using 300 nanosecond duration pulses at 30,000 V the authors were able to ablate liver tumors within 0.5 cm of critical structures such as the portal vein, hepatic vein, biliary tree, or gastrointestinal tract.…”
Section: E174mentioning
confidence: 99%
“…Initial trials in humans have also demonstrated the feasibility of nsPEF for the treatment of other cutaneous lesions such as seborrheic keratosis and sebaceous gland hyperplasia [76,77]. Clinical studies on applications for visceral organs are limited; however, Liu and colleagues [78] have trialed nsPEF for treating hepatocellular carcinoma (HCC) in 15 patients [79]. Using 300 nanosecond duration pulses at 30,000 V the authors were able to ablate liver tumors within 0.5 cm of critical structures such as the portal vein, hepatic vein, biliary tree, or gastrointestinal tract.…”
Section: E174mentioning
confidence: 99%